Independent Curriculum Implementation Training for Students of the Elementary School Teacher Education Study Program at SDN 3 Baubau - Samritin; Kamarudin; Irwan; Azaz Akbar (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
Changing the curriculum is something that must be done by a country along with the times. Curriculum changes in Indonesia have been made several times. The results of the latest curriculum changes have resulted in the Independent Curriculum. Curriculum changes are expected to have a significant positive impact on learning and outcomes. However, curriculum changes also provide flexibility to teachers who carry out learning in the classroom. Students of the Teacher Education Study Program of the University of Muhammadiyah Buton as prospective teachers need to be equipped with experience before they become teachers. This training activity aims to provide experience to participants implementing the independent curriculum. The activity was attended by 12 students as training participants. In general, this training activity is carried out in three stages: the presentation of material, training, and evaluation of results. The presentation of the material uses the lecture and question and answer method, the practice uses the tutoring method, and the evaluation of the results uses the observation method. The evaluation results showed that the average ability of participants to compile learning tools was 88.44%, the average ability to carry out learning reached 90.56, and the personality of participants reached 92.88. Based on the analysis of the results of the discussion, it was concluded that this training activity has had a very satisfactory impact on the ability of trainees in the implementation of the independent curriculum in elementary schools.